Chemical Composition and Effect of Feeding Different Levels of Sugarcane Tops with Concentrate Mixture/ Mustard Cake on Digestibility in Buffalo Calves - Sharma, Vijay Kumar; Tomar, S K; Kundu, S S; Jain, Pankaj; Jha, Pankaj; Kumar, Muneendra; Lata, Manju (Indian Journal of Dairy Science, 2012)
The present study was conducted to evaluate the nutritive value of the sugarcane tops (SCT) of the elite clones as fodder. Initially proximate analysis of the 28 varieties of the SCT for the three cuts was done and the variety no. CoJ-64 was found to have highest crude protein content. The total gas content of the different varieties varied between 31.8 to 56.2 ml, 29.25 to 55.1 ml, 28.75 to 54.5 ml for 1st (early), 2nd (mid) and 3rd (late) harvesting stage cut respectively and there was significant difference (p